ANALISIS KONSUMEN TERHADAP JUAL BELI DI E-COMMERCE DALAM HUKUM ISLAM - Raja Nasrullah Fajrillah; Alif Alyasin Sipahutar (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2023)
This research aims to analyze consumer behavior in the context of buying and selling in e-commerce, considering the perspective of Islamic law. In today's digital era, e-commerce has become a popular platform for consumers to engage in transactional activities. However, from the standpoint of Islamic law, there are questions regarding the validity and conformity of buying and selling practices in e-commerce with Sharia principles. This study adopts a qualitative approach, collecting data through in-depth interviews with e-commerce consumers who identify as Muslims. We analyze their perspectives on beliefs, motivations, and experiences in conducting buying and selling transactions on e-commerce platforms. The findings reveal that while there are diverse views and understandings of Islamic law in the context of e-commerce, the majority of consumers prioritize convenience, speed, and ease in online shopping. Nevertheless, there is also an awareness of the importance of ensuring the halal (permissible) nature and fairness of buying and selling transactions. In response to these issues, we recommend improved education on Islamic law related to buying and selling in e-commerce, targeting both consumers and e-commerce platform owners. Additionally, relevant stakeholders such as scholars and regulators should play an active role in providing clear guidelines and fatwas (legal opinions) regarding buying and selling practices in e-commerce that align with Islamic law principles. This research contributes significantly to understanding consumer behavior in buying and selling within e-commerce from the perspective of Islamic law. The findings are expected to provide valuable insights for the development of e-commerce grounded in Sharia principles while respecting consumer needs.Keywords: Consumer Analysis, Buying, and Selling, E-Commerce